Complications of diabetes - Chawla, Rajeev (Jaypee Brothers Medical, 2012)
Complications of Diabetes is a concise reference introducing clinicians to the possible complications with diabetes. It stresses the need for early detection and covers all complications occurring in different parts of the body. Beginning with an overview of acute and chronic complications of diabetes, separate chapters discuss renal complications, ocular complications, foot complications, diabetes and coronary artery disease and diabetes and cerebrovascular disease.